Power Quality Performance Analysis of grid tied PV fed Parallel Pumping System under Normal and Vibrating Condition. (July 2018) - Shankar, V.K. Arun; Umashankar, S.; Sanjeevikumar, P.; Mihet-Popa, Lucian; Fedák, Viliam; Ramachandaramurthy, Vigna K.
Abstract: The aim of this paper is to perform the relative study of power quality problems in a grid tied solar PV system, with and without vibration connected to a parallel pumping system at 1.0 bar set pressure by using two control techniques such as VVC+ & V/f. In case of vibrations, the effect of motor vibration problems on the dynamic performance and electrical power quality of water pumping system will be observed. Vibrations are introduced in the pumping system by loosening the base plate of the pumps. During motor vibrations, the instantaneous flicker values become high which leads to variation in the supply voltage and torque imbalance. The effect of power quality parameters in a solar feeder during normal conditions and vibrating conditions are analysed. In normal condition, the THD increases and the flicker is high only during transient period due to sudden voltage variations. A comparison has been made to observe the appropriate control method for pumping system with and without vibrations in a solar PV-grid connected system.